Dynamic study of supratentorial gliomas with L-methyl-11C-methionine and positron emission tomography. - Lilja, A; Bergström, K; Hartvig, P; Spännare, B; Halldin, C; Lundqvist, H; Långstrom, B (American Journal of Neuroradiology, 1985)
The regional kinetics of intravenously injected L-methyl-11C-methionine (11C-L-methionine) in the brain was investigated by positron emission tomography (PET) in 14 patients with gliomas. In both tumor and unaffected brain the tracer uptake reached a nearly constant level in 5 min or less. The ratio between the uptake of 11C-L-methionine by high-grade tumors and the uptake by unaffected brain was 1.9-4.8. In two cases of low-grade astrocytoma the ratio was 0.8-1.0. High uptakes of 11C-L-methionine occurred in gliomas even in the absence of blood-brain barrier defects as observed by other methods. This indicates that besides active transport of amino acid, a larger extracellular space in tumor as compared with unaffected brain tissue may also contribute to the increased uptake of 11C-L-methionine--derived radioactivity. In some patients delineation of the tumors was improved by use of PET with 11C-L-methionine as compared with computed tomography, angiography, and, in some instances, PET with 68Ga-EDTA. PET with 11C-L-methionine permits better evaluation of the tumor extent and may affect preoperative grading.